Pengawasan Mutu Beras pada Perusahaan Umum BULOG Divisi Regional Bali - MAHENDRA, PUTU RAKA; DEWI, RATNA KOMALA; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.3, Juli 2016, 2016)
Rice Quality Supervision On Regional Division BULOG Public Company Bali The purpose of this study to determine the performance of the quality controlconducted by Perum Bulog Division Bali and quality control analysis usingstatistical quality control approach that maps the control and quality cost. Researchmethods using primary data from some respondents that the head of production,head of marketing and head of the administration. Secondary data were obtainedfrom research journals, internet, papers and books. Quality inspection on thecontent of the rice is to pour the rice from the sample. In the storage phase is alsotaken care by performing the spraying and fumigation. Based on the control chart isshown that the data obtained are not entirely within the control limits that have beenestablished that there are a few months out of the upper control limit covering Julyand August. Quality control using the cost of the quality of the company is stillloose, because the real quality cost incurred is Quality Control Cost Rp4.478.218.605, Quality Assurance Cost Rp 39.484.680.000, and Total Quality CostRp 43.962.898.605 with the extent of damage of 4.492 tons, larger than theoptimum quality cost Quality Assurance Cost is Rp 13.304.337.284, QualityAssurance Cost Rp 13.290.480.000, and Total Quality Cost Rp 26.594.817.284with the level of damage by 1.512 tons.
Keywords: rice; quality control; statistical quality control